Morphology and genetic characterization of amnesic shellfish toxin producing diatom species, Pseudo-nitzschia and Nitzschia (Bacillariophyceae) in Malaysian waters / Tan Suh Nih - Tan , Suh Nih (2019)
Diatom Pseudo-nitzschia and Nitzschia are widely distributed in brackish and marine environments. Some species are known to produce the neurotoxin domoic acid (DA) that responsible for Amnesic Shellfish Poisoning (ASP) in humans and marine organism. While several species have been reported to be toxic in Malaysian waters, there was no confirmed ASP case reported thus far. In this study, samplings were conducted throughout the coastal and mangrove waters of Malaysia to determine the occurrence, distribution and toxicity of Pseudo-nitzschia and Nitzschia species. A total of 548 strains of Pseudo-nitzschia and Nitzschia were established and identified by light and electron microscopy; they are P. batesiana, P. bipertita, P. brasiliana, P. circumpora, P. cuspidata, P. fukuyoi, P. pungens, and N. navis-varingica. Species identification in Pseudo-nitzschia based sorely on morphological characters is challenging owing to the minute morphological differences. Thus, molecular characterization has become an essential supporting criterion in species delineation. In this study, the phylogenetic relationships of Pseudo-nitzschia species were inferred based on three genetic markers. A pair of genus-specific primer targeting cox1 gene were developed in silico. The results revealed three distinct clades in the P. pseudodelicatissima complex, while the P. delicatissima complex formed a distinct clade (Group IV) in both the LSU and ITS2 phylogeny. ITS2 dataset resulted in the most resolved trees, followed by cox1 and LSU. For the benthic diatom Nitzschia navis-varingica, it was found widely distributed in the brackish mangrove areas of Malaysia. To examine the potential ontamination of DA in the local shellfish industry, both the N. navis-varingica strains and shellfish collected were analyzed by FMOC-LC-FLD and LC-MS/MS. DA and its geometrical isomers, isodomoic A and B, were detected in 48 strains of N. navis varingica. Their cellular DA content ranged from 0.37–11.06 pg/cell. For the 25 shellfish samples analyzed, only two cockle samples from Asajaya, Sarawak were detected with 283.72 and 465.04 µg/kg, respectively. To understand the population dynamics of N. navis-varingica in the Western Pacific, the genetic diversity was investigated using LSU rDNA and ITS2 markers. The LSU dataset revealed high sequence homogeneity among all strains examined (0–0.9%). The ITS2 inferences identified eight distinct clades, with high sequence heterogeneity (0.5–19.7%); analysis of haplotype diversity recovered 44 haplotypes. Our results showed strong gene flow among N. navis-varingica populations in the Western Pacific region (ФST=0.48095). However, isolates from Vietnam and Japan formed a distinct haplotype H3 (FST, 0.41–1.00), suggesting possible genetic structuring between the water bodies of northwestern Pacific and the South China Sea (SCS). It is speculated that ocean current circulations (SCS and Kuroshiro currents) may play a role in this allopatric differentiation of N. navis-varingica. This study has demonstrated the occurrence and wide distribution of the toxigenic Pseudo-nitzschia species and N. navis-varingica in Malaysian waters. The potential ASP risk of in Malaysia should be assessed continuously by monitoring the toxic plankton and level of DA in shellfish mollusks to safeguard public health and ensure seafood safety.